2021
DOI: 10.1016/j.acra.2021.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Radiologist User Study for Artificial Intelligence-Guided Grading of COVID-19 Lung Disease Severity on Chest Radiographs

Abstract: Rationale and Objectives: Radiographic findings of COVID-19 pneumonia can be used for patient risk stratification; however, radiologist reporting of disease severity is inconsistent on chest radiographs (CXRs). We aimed to see if an artificial intelligence (AI) system could help improve radiologist interrater agreement. Materials and Methods:We performed a retrospective multi-radiologist user study to evaluate the impact of an AI system, the PXS score model, on the grading of categorical COVID-19 lung disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, there is no standardized method in reporting CXR findings in terms of disease severity. Li et al used the pulmonary x-ray severity (PXS) score, a DL-based algorithm providing quantitative measures of COVID-19 severity on CXR, as an adjuvant tool to radiologists' work-which, however, always decided on the severity grading and definitive radiological report-, and noticed an improvement in the assessment of the severity on a 4-point scale (normal/minimal, mild, moderate, severe) and in the inter-reader agreement, with no need for radiologists' training on the use of the score [59,60]. Li et al also found that the severity scores were significantly associated with intubation/death within 3 days from the admission, in CXR rated moderate or severe [59].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest X-raymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no standardized method in reporting CXR findings in terms of disease severity. Li et al used the pulmonary x-ray severity (PXS) score, a DL-based algorithm providing quantitative measures of COVID-19 severity on CXR, as an adjuvant tool to radiologists' work-which, however, always decided on the severity grading and definitive radiological report-, and noticed an improvement in the assessment of the severity on a 4-point scale (normal/minimal, mild, moderate, severe) and in the inter-reader agreement, with no need for radiologists' training on the use of the score [59,60]. Li et al also found that the severity scores were significantly associated with intubation/death within 3 days from the admission, in CXR rated moderate or severe [59].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest X-raymentioning
confidence: 99%
“…Li et al used the pulmonary x-ray severity (PXS) score, a DL-based algorithm providing quantitative measures of COVID-19 severity on CXR, as an adjuvant tool to radiologists' work-which, however, always decided on the severity grading and definitive radiological report-, and noticed an improvement in the assessment of the severity on a 4-point scale (normal/minimal, mild, moderate, severe) and in the inter-reader agreement, with no need for radiologists' training on the use of the score [59,60]. Li et al also found that the severity scores were significantly associated with intubation/death within 3 days from the admission, in CXR rated moderate or severe [59]. Mushtaq et al reported in their retrospective study that an AI-powered severity score based on the percentage of pixels involved by opacity or consolidation for each lung at the CXR, adjusted at the multivariate analysis for demographics and comorbidities, showed that a value ≥30 at the hospital admission CXR was an independent predictor for mortality and ICU admission for COVID19 (p < 0.001), and found a significant link with admission pO2/FiO2 levels [61].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest X-raymentioning
confidence: 99%
“…Recently, Li et al (11) carried out a multi-reader study for the grading of COVID-19 in chest radiography and observed that the AI system improved radiologist performance. Since the deep learning technique has been found useful in the diagnosis of COVID-19 (12,13), combining radiologist interpretation with the DL approach gives a promising result for the detection of COVID-19 (13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, multiple groups have developed AI tools to grade lung disease severity on chest radiographs [28][29][30]; AI-determined severity scores have been correlated with clinical outcomes such as intubation and death [30]. Such AI tools have also been used to improve the interrater agreement of radiologists evaluating COVID-19 lung disease severity on chest radiographs [31].…”
Section: Accepted Manuscript Covid-19 Disease Severitymentioning
confidence: 99%